1991
DOI: 10.1042/cs0810471
|View full text |Cite
|
Sign up to set email alerts
|

Urinary excretion of digoxin-like immunoreactive factor and arginine-vasopressin in hyper- and hypo-thyroid rats

Abstract: 1. Urinary excretion of digoxin-like immunoreactive factor and arginine-vasopressin and other parameters related to salt and water metabolism were studied in hyper- and hypo-thyroid rats after different tests. 2. Urinary excretion of arginine-vasopressin was increased in hyperthyroid and reduced in hypothyroid rats with respect to controls, in response to water deprivation or a hypertonic saline load. 3. Control and hypothyroid rats showed the highest urinary excretion of digoxin-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
20
2

Year Published

1994
1994
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 20 publications
(16 reference statements)
3
20
2
Order By: Relevance
“…Medullary NO plays a major role in the renal regulation of sodium and water excretion and therefore in the control of arterial blood pressure (8,9). The normal values in medullary NOS activity in our hypothyroid rats indicate that the medulla has an adequate capacity to synthesize NO, which is consistent with the normal sodium handling of hypothyroid rats under normal conditions and after several challenges (6,7). The high NOS activity in the renal cortex of hyperthyroid rats may be secondary to the hyperdynamic circulation of these animals, because cortical NOS activity is mainly produced by constitutive endothelial NOS (33).…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Medullary NO plays a major role in the renal regulation of sodium and water excretion and therefore in the control of arterial blood pressure (8,9). The normal values in medullary NOS activity in our hypothyroid rats indicate that the medulla has an adequate capacity to synthesize NO, which is consistent with the normal sodium handling of hypothyroid rats under normal conditions and after several challenges (6,7). The high NOS activity in the renal cortex of hyperthyroid rats may be secondary to the hyperdynamic circulation of these animals, because cortical NOS activity is mainly produced by constitutive endothelial NOS (33).…”
Section: Discussionsupporting
confidence: 54%
“…Hyperthyroidism increases the responsiveness of resistance vessels to the endothelium-dependent vasodilator, acetylcholine, whereas methimazole-induced hypothyroidism attenuates the endothelium-dependent response (5). Thyroid dysfunctions also affect cardiac and renal weight as well as renal sodium handling (2,6,7). Thus, hyperthyroidism occurs with a reduced sodium excretion after a saline load (7) and a blunted pressure -diuresis -natriuresis (PDN) response (6, 7) whereas, in hypothyroidism, a normal sodium excretion (7) or a tendency to sodium loss (2) have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…30 This mechanism might increase peripheral resistance and therefore increase BP. Moreover, hyperthyroidism affects renal sodium handling in rats, 2,5,6 reduces sodium excretion after a saline load, 5 and blunts the pressure-diuresisnatriuresis response. 6 These antinatriuretic effects might be aggravated by NO deficiency 9,10 and contribute to producing a displacement to the right in the set point of the pressurediuresis-natriuresis relation, as indicated by the normal sodium excretion with increased BP in the T 4 ϩL-NAMEtreated group.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Animal studies have reported a dose-and time-related increase in arterial pressure 5,6 and have shown that the hyperthyroid state affects cardiac and renal weight and reduces renal sodium excretion. 2,5,6 It is well known that nitric oxide (NO) plays a major role in the regulation of vascular tone, 7 renal sodium excretion, 8,9 and therefore, of arterial blood pressure (BP). 10 Both acute and chronic administration of NO synthase (NOS) inhibitors increase systemic arterial BP.…”
mentioning
confidence: 99%
“…Some authors have found high plasma AVP and postulate the role of this hormone in the development of hyponatremia of hypothyroidism (Skowsky & Kikuchi 1978, Laczi et al 1987. Others have found that plasma AVP is normal or even suppressed (Iwasaki et al 1990, Vargas et al 1991, Arnaout et al 1992, Ota et al 1994. Probably the discrepancies are due to the different characteristics of the individuals studied, principally the duration and severity of the hypothyroidism, which may cause an increase in plasma AVP by raising non-osmotic stimuli.…”
Section: Discussionmentioning
confidence: 90%